PENGARUH PUPUK KANDANG AYAM TERHADAP SERAPAN NITROGEN OLEH TANAMAN KUBIS BUNGA (Brassica oleracea L.) PADA OXIC DYSTRUDEPTS LEMBANTONGOA - Asni Afianti Makka; Yosep Soge Patadungan; Sri Wahidah Prahastuti (Universitas Tadulako, 2015)
This research aimed to determine the effect of poultry manure on nitrogen uptake of cabbage (Brassica oleracea L.)plant grown on Oxic Dystrudpets Lembantongoa. This research used a Randomized Block Design (RBD) consisting of sevenrates of poultry manure i.e. Control, 10 t ha-1, 20 t ha-1, 30 t ha-1, 40 t ha-1,50 t ha-1, and60 t ha-1. Eachtreatmentwas replicated3 times, sothere were 21experimental units.If Analysis of variance of data showed a significant effect, then the data was tested further using honestly significant differenceat 5 % (HSD 5%). The results ofthis study indicatedthat the use ofvariousrates ofpoultry manure couldincreaseplant dry weightas shown bya linearequation y = 0.338x + 51.90 with R2 = 0.919, consistent withincreased levels ofNin theplant tissuewiththe linearequation y = 0,035x + 0,022 with R2 = 0,994 andN uptakewiththe equation y = 0,026x - 0,055 (R2 = 0,985). The highestN uptakewas obtainedin theapplication of60tha-1poultry manure.Key words : Poultry manure, N uptake, Oxic Dystrudepts.